Effectiveness of castor oil extract on Escherichia coli and its endotoxins in root canals - Valera, Marcia Carneiro [UNESP]; Maekawa, Lilian Eiko [UNESP]; Chung, Adriana; Oliveira, Luciane Dias de; Carvalho, Claudio Antonio Talge [UNESP]; Koga-Ito, Cristiane Yumi; Jorge, Antonio Olavo Cardoso [UNESP] (My University, 2012)
The results of the present study showed a significant decrease in the number of E. coli in root canals (first collection) after irrigation with castor oil extract during biomechanical preparation. All medications tested in this study were able to eliminate E. coli in root canals; however, they could not neutralize endotoxins completely.
Keywords: antiinfective agent; biomedical and dental materials; calcium hydroxide; castor oil; chlorhexidine; chromogenic substrate; diagnostic agent; endotoxin; endotoxin, Escherichia coli; lipopolysaccharide; plant extract; polymyxin B; sodium chloride; topical antiinfective agent; bacterial load; comparative study; controlled clinical trial; controlled study; drug antagonism; drug effect; Escherichia coli; human; Limulus lysate test; materials testing; microbiology; randomized controlled trial; time; tooth pulp; Anti-Bacterial Agents; Anti-Infective Agents, Local; Bacterial Load; Calcium Hydroxide; Castor Oil; Chlorhexidine; Chromogenic Compounds; Dental Pulp Cavity; Endotoxins; Humans; Limulus Test; Lipopolysaccharides; Materials Testing; Plant Extracts; Polymyxin B; Root Canal Irrigants; Sodium Chloride; Time Factors